Death to the Coral Reefs and More Money for Everybody Else (The Scientific World Journal)
It was a bad week for the residents of the world’s rapidly disappearing coral reefs, says Science in its lead story. But it was a good week to be a mathematician. NSF director Rita Colwell proposed tripling their research budget, reports Nature’s lead story.